2022
DOI: 10.1093/ije/dyac076
|View full text |Cite
|
Sign up to set email alerts
|

Identifying factors contributing to increased susceptibility to COVID-19 risk: a systematic review of Mendelian randomization studies

Abstract: Background To summarize modifiable factors for coronavirus disease 2019 (COVID-19) suggested by Mendelian randomization studies. Methods In this systematic review, we searched PubMed, EMBASE and MEDLINE, from inception to 15 November 2021, for Mendelian randomization studies in English. We selected studies that assessed associations of genetically predicted exposures with COVID-19-related outcomes (severity, hospitalization a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 123 publications
4
31
1
Order By: Relevance
“…This was supported by multiple MR studies and our analysis, which included BMI as the supplementary exposure. Other studies also assessed multiple anthropometric traits, including waist circumference, hip circumference, waist-to-hip ratio, and trunk fat ratio as well as BMI to evaluate the effect of adiposity on the risk of COVID-19 (7,8,13,14,(25)(26)(27)(28)(29)(30)(31). These MR studies consistently estimated that increases in BMI, waist circumference, and hip circumference are causal for COVID-19 severity (7,13,14,26,28).…”
Section: Discussionmentioning
confidence: 99%
“…This was supported by multiple MR studies and our analysis, which included BMI as the supplementary exposure. Other studies also assessed multiple anthropometric traits, including waist circumference, hip circumference, waist-to-hip ratio, and trunk fat ratio as well as BMI to evaluate the effect of adiposity on the risk of COVID-19 (7,8,13,14,(25)(26)(27)(28)(29)(30)(31). These MR studies consistently estimated that increases in BMI, waist circumference, and hip circumference are causal for COVID-19 severity (7,13,14,26,28).…”
Section: Discussionmentioning
confidence: 99%
“…Family support and a herd mentality can help improve vaccination among the undecided [11]. Other family characteristics, such as living alone, without a partner or children, and being single, were negatively associated with the desire to be vaccinated [34][35][36]. People living alone with limited care may have less access, irregular preventive health visits, and less support from family members [37].…”
Section: Socioeconomic Level and Family Psychosocial Problemsmentioning
confidence: 99%
“…Comorbidities: No strong evidence has been found, and studies showing conflicting results, whether certain diseases (including diseases of the circulatory, digestive, nervous, respiratory, genitourinary, musculoskeletal, and connective tissue systems, metabolic diseases, and mental disorders) increase the risk of COVID-19 [36]. Like all infectious processes, the clinical severity depends on the virulence of the microorganism and the susceptibility of the host.…”
Section: Sex and Agementioning
confidence: 99%
“… 5 Moreover, a meta-analysis found six Mendelian randomization studies which consistently demonstrated ‘strong associations of smoking traits, including smoking initiation, smoking heaviness and lifetime smoking index (which combined smoking initiation, duration, heaviness and cessation), in the risk of COVID-19 severity, hospitalzation and mortality’, and the authors suggested that the mechanism may be ‘an increased expression of ACE2, a receptor for SARS-CoV-2 in the airway epithelium’ in smokers. 6 …”
Section: Interpreting the Wider Evidence Basementioning
confidence: 99%